A questão da técnica moderna em Heidegger, a partir do habitar e ser na Amazônia - Lopes, Ronnielle de Azevedo (2015)
The present essay has as its scope to reflect upon the technique in Martin Heidegger as the main matter in order to comprehend our time. To Heidegger, in contemporaneity, technique cannot be simply related to causal relations and even less characterized as a means towards an end. The modern technique can neither be considered a mere instrument controllable as humanity wishes. The technique matter to the thinker must be conceived from its essence, which to Heidegger is not technique at all. In his thoughts, regarding the technique essence, Heidegger outlines his criticism to modernity. According to the philosopher, the modern technique is a way of uncovering the totality of the entities which is imposed in the provocation of the entities as a constant, objectifiable and estimable availability of the man, his subject and sir. Heidegger within his criticism proposes an alternative, the technique absolutizing, a new way of thinking, from a habitar originated in Earth. In this sense, this essay seeks to think the technique matter in Heidegger in the unfolding intrinsic to the Tocantins-Araguaia valley, in Eastern Amazon, in Para s south-southeast. We comprehend that the communities integrated to local environment in this region assume and teach a deep sense in what Heidegger called habitar